The Effect of Whole Body Vibration Training and Detraining Periods on Neuromuscular Performance in Male Older People - Ali Abbasi; Hossein Berenjeian Tabrizi; Kambiz Bagheri; Alireza Ghasemizad (University of Social Welfare & Rehabilitation Sciences, 2011)
Objectives: This study aimed to evaluatethe the effect of eight weeks whole body vibration training (WBVT) and detraining periods on neuromuscular performance male healthy older people. Methods & Materials: Thirty male subjects (70±9.6 years old) were randomly allocated into two groups of WBVT and control (n=15 per group). Timed Up & Go and 5-Chair stand tests, as indicators of neuromuscular performance in older subjects, were taken as pretest and posttest and also after four, six, and eight weeks of detraining. Results: Results of Repeated-measure ANOVA and one-way ANOVA showed that neuromuscular performance improved significantly in WBVT group (P<0.05). There were also significant differences between posttest and six and eight weeks of detraining periods in WBVTgroup (P<0.05). Conclusion: WBVT could affect neuromuscular performance in healthy subjects and reduce the probability of falling among them. However, the effects of this training are not persistent, goes back to the early levels after six weeks of detraining. Hence, it is possible that WBVT can be recommended as a safe balance training to older people.